Concern for Public Health Education with Hygiene and Clean Water Using Posters and Leaflets - Vina Yulia Anhar; Pradiptha Hulanda Saputra; Nur Khalishah; Radiatul Isnaniah; Siti Faridah Suhendri Nurputri (Jurnal Berkala Kesehatan, 2023)
Hives Disease is the most common complaint experienced by the community. The cause of hives is due to a lack of clean and healthy living habits. Besides that, the main factor for the many hives is because the quality of the water in the village is very bad, the lack of clean water supply is also the reason because almost all residents there bathe with well water where the water is colored, tastes and smells. This study aims to analyze the increase in public knowledge before and after receiving education. Methods: This research is a quantitative  research with observation and interview methods. The sample is 33 people who fit the inclusion criteria. Data analysis using the Wiloxon Ranks test. The degree of error used is = 0.05. Results: It is known that the p-value = 0.205 <0.05, which means that there is no significant difference between the pre-test and post-test group scores. Conclusion: Based on these results it can be concluded that there is an increase in knowledge that is not significant in the community